Serological evidence of exposure and possible Taenia solium larval infection in Orang Asli communities of Peninsular Malaysia - Sahu, P. S.; Lim, Y.A.L.; Romano, Ngui; Rohela, Mahmud (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2016)
Orang Asli communities are known as aborigines of peninsular Malaysia who are underprivileged and also known to be carriers of many different parasitic infections. However, the possible burden of cysticercosis (caused by Taenia solium larvae or Cysticercus cellulosae) has never been explored in these communities. Objective of this study was to explore the seroprevalence of human cysticercosis among Orang Asli (subgroups: Semelai, Semai Pahang, Temuan, Orang Kuala, Temiar, Semai Perak, and Mah Meri) communities. In this preliminary study, both male and female of all age groups (1 to 68 years) were screened for T. solium larvae specific antibodies in sera employing a commercially procured IgG-ELISA kit. Sera from a total of 522 randomly chosen Orang Asli individuals were screened between July to December 2013. A total of 20 (3.8%) subjects were diagnosed positive for anti-Cysticercus antibodies (95% CI: 2.5% – 5.8%; χ2=17.8; p<0.05). The prevalence of antibody positivity ranged between 0.9% (Semelai subgroup) to 9.9% (Orang Kuala subgroup). Statistical significance was observed between the low income status of family and seropositivity for cysticercosis (p=0.041) based on univariate analysis. Present study findings indicated that exposure to T. solium larval infection might have occurred in the aborigine communities from peninsular Malaysia. Results could only suggest that cysticercosis is an under recognized health problem here. Therefore a regional public health surveillance program might help verifying further the risk factors of T. solium cysticercosis targeting a larger population in both peninsular and East Malaysia.